PERTANGGUNGJAWABAN PIDANA PERUSAHAAN ANGKUTAN UMUM KETIKA TERJADI KECELAKAAN LALU LINTAS (Jurnal De Jure Muhammadiyah Cirebon, 2024)
Every land transportation accident always causes losses only to users, both moral and material. Especially accidents involving public transportation. Public transportation companies pay little attention to aspects of security, comfort, safety, affordability, equality and regularity of passengers. This research uses a normative juridical research type with a problem formulation, namely: How is the legal protection for public transportation consumers when a traffic accident occurs and what is the criminal liability of public transportation companies in the  of a traffic accident.The research results are as follows: Legal protection for consumers/users of public transportation services is regulated in Law Number 8 of 1999 concerning Consumer Protection and in Law Number 22 of 2009 concerning Road Traffic and Transportation. In the context of the legal system in force in Indonesia, efforts or means that can be used to fight for people's rights can be achieved by implementing legal and criminal sanctions, in addition to This can also be done by filing a civil lawsuit with the court, or resolving the case through non-litigation channels, namely resolving disputes outside the court through the intermediary of other parties whose existence has been regulated in statutory regulations. Theoretically, public transport companies can be held criminally liable in the event of accidents caused by vehicle unfitness. However, this cannot be done in practice because the law does not clearly regulate in what cases and when a public transportation company can be said to have committed a criminal act.Keywords: Criminal Liability, Public Transportation Company, Traffic Accidents